Simulação no ensino de emergências respiratórias - Teixeira, Felipe de Oliveira (2014)
Education through simulation of real treatment has been proved a very useful tool in medical courses. Advantages of this methodology include safe environment for learning, possibility of error without any risk to patients and the development of various skill categories. The use of high-fidelity mannequins simulators (robots) is a good example of simulation can be employed for teaching several situations, like medical emergencies care. Objective: The aim of this study was to evaluate the contribution of teaching methods that employ the use of simulator respiratory emergencies within an elective curriculum for 3rd year`s medicine students. The secondary objective was assess the adequacy of the use of simulators for teaching skills in respiratory emergencies. Material and Methods: An elective course was created for 3rd year students of medical school of PUCSP for teaching respiratory emergencies, and for its practical part students, had the opportunity to simulate the treatment through the use of computerized mannequins, that was used for the realization of "pharmacological and surgical" procedures. After each activity simulation was held a debriefing where we discussed the action of students participating in simulated activitie. A pre and post test was conducted prior and after the course, with 29 questions (tests) related on respiratory emergencies theme. At the two weeks, students responded to a structured survey about the quality of the course. Results: There was a significant increase in the level of correct post-test (70.2%), when the results were compared to the pre-test (53.3%, p≤0,05). The questionnaire on the quality of the course had a positive result (41 to 48 points of 50 possible). Discussion: The analysis of the tests conducted before and after the course showed that there were more significant increase in correct answers after the course when the questions were related to matters discussed widely in practical classes during the course. Conclusion: We concluded that the simulation activities are an efficient way to improve the level of knowledge of respiratory emergencies of third year students of medicine, especially in relation to the practical content. We also conclude that the robots in simulation activities were very well evaluated by students